Analytical profiles of drug substances. - Brittain, H. G. (Analytical profiles of drug substances, 1994)
Although the official compendia define a drug substance as to identity, purity, strength, and quality, they normally do not provide other physical or chemical data, nor do they list methods of synthesis or pathways of physical or biological degradation and metabolism. Such information is scattered throughout the scientific literature and the files of pharmaceutical laboratories. Edited by the Associate Director of Analytical Research and Development for the AmericanAssociation of Pharmaceutical Scientists, Analytical Profiles of Drug Substances and Excipients brings this information together into one source. The scope of the series has recently been expanded to include profiles of excipient materials.